Sorption of vanadium (V) onto natural soil colloids under various solution pH and ionic strength conditions. (February 2017) - Luo, Xiuhua; Yu, Lin; Wang, Changzhao; Yin, Xianqiang; Mosa, Ahmed; Lv, Jialong; Sun, Huimin
Abstract: Batch sorption kinetics and isothermal characteristics of V(V) were investigated on three natural soil colloids (manual loessial soil colloid (MSC), aeolian sandy soil colloid (ASC), and cultivated loessial soil colloid (CSC)) under various solution pH and ionic strength (IS) conditions. Colloids were characterized by atomic force microscopy (AFM), X-ray diffraction (XRD), and fourier transform infrared spectroscopy (FTIR). AFM micrographs showed CSC with an aggregated shape with larger particle diameter as compared with ASC and MSC. XRD spectra revealed the presence of different minerals in natural soil colloids including biotite, kaolinite, calcite and quartz, which might contribute to sorption process. The sorption ability decreased with increase of colloidal particle size. The sorption was mainly attributed to complexation by active carboxylate and alcohol groups of colloidal components. Sorption kinetics and isotherms of V(V) onto natural soil colloids were best fitted with Pseudo-second-order and Freundlich models. Langmuir model indicated that sorption capacity of MSC and ASC was comparable (285.7 and 238.1 mg g −1 ); however, CSC exhibited the lowest sorption capacity (41.5 mg g −1 ) due to its larger particle diameter and aggregated shape. The maximum V(V) sorption capacity reached plateau values at a solution pH ranged between 5.0 and 9.0 for MSC and ASC, and 6.0–8.0 for CSC. Sorption capacity of V(V) onto natural soil colloids decreased with increasing IS. Based on result of this study we can conclude that sorption of V(V) onto natural soil colloids is pH- and IS-dependent. These findings provide insights on the remediation of vanadium-contaminated soils. Highlights: Natural soil colloids were characterized by AFM, XRD, and FTIR analyses. Active carboxylate and alcohol groups domonated the V(V) adsorption. High ionic strength decreased the sorption capacity of V(V) adsorption.